2022
DOI: 10.3389/fcimb.2022.1038928
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for constipation in Parkinson’s: A systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundParkinson’s disease (PD)-related constipation may affects both disease occurrence and disease progression. Probiotics, as a potential therapeutic intervention, have attracted the attention of researchers, but the evidence of their efficacy and safety has not been systematically reviewed.AimA systematic review and meta-analysis of randomized controlled trials of probiotics in the treatment of PD constipation was conducted to determine the efficacy and safety of probiotics in the treatment of PD consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Compared to the control group, probiotics increased weekly defecation frequency in PD patients. In contrast, PD patients treated with probiotics had similar stool consistency to those given a placebo (Yin and Zhu, 2022). Another meta-analysis of eleven trials found compelling evidence of age-related reductions in both motor and non-motor symptoms, depression, and gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the control group, probiotics increased weekly defecation frequency in PD patients. In contrast, PD patients treated with probiotics had similar stool consistency to those given a placebo (Yin and Zhu, 2022). Another meta-analysis of eleven trials found compelling evidence of age-related reductions in both motor and non-motor symptoms, depression, and gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term safety of microbiota-targeted therapies in PD has yet to be thoroughly evaluated. While preliminary studies regarding the impact of probiotics on GI and motor symptoms have rendered promising results [62][63][64], longterm efficacy and safety studies [65], levodopa interaction risk evaluations [15], as well as therapeutic dose identification [62,66] are necessary. In comparison, FMT studies are more heterogeneous methodologically despite the limited data available on PD models [44]; some short-term studies attest to its effectiveness in treating gastrointestinal dysfunction and improving motor symptoms [45,46,67,68].…”
Section: Clinical Translation Of Rodent Studies On Microbiota-targete...mentioning
confidence: 99%
“…Of these, only five trials have been completed; so far, only four of them (NCT04389762, NCT04451096, NCT03377322, and NCT02459717) have released the results obtained [ 184 , 185 , 186 , 187 ], whereas the fifth one (NCT01536769) has not. A recent meta-analysis analyzed the results of the clinical trials NCT04451096, NCT03377322, and NCT02459717 plus an additional study [ 188 ] and concluded that there is insufficient evidence supporting the use of probiotics to treat constipation in patients with PD; however, it also recognized that, according to the limited evidence available, probiotics have potential value in the treatment of PD-related constipation [ 189 ].…”
Section: Intestinal Microbiota and Pdmentioning
confidence: 99%